2014
DOI: 10.1002/2014gc005569
|View full text |Cite
|
Sign up to set email alerts
|

Influence of late Pleistocene glaciations on the hydrogeology of the continental shelf offshore Massachusetts, USA

Abstract: Multiple late Pleistocene glaciations that extended onto the continental shelf offshore Massachusetts, USA, may have emplaced as much as 100 km 3 of freshwater (salinity <5 ppt) in continental shelf sediments. To estimate the volume and extent of offshore freshwater, we developed a three-dimensional, variable-density model that couples fluid flow and heat and solute transport for the continental shelf offshore Massachusetts. The stratigraphy for our model is based on high-resolution, multichannel seismic data.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(48 citation statements)
references
References 54 publications
3
44
0
Order By: Relevance
“…They thus conclude that the fresh water beneath the middle shelf was most likely transported there from onshore along seaward‐dipping groundwater aquifers extending all the way to the coast, a total distance of ~50–70 km. This conclusion was recently supported by the electromagnetic study of Gustafson et al (), which was conducted at both the Martha's Vineyard and New Jersey transects studied by Siegel, Lizerralde, et al (), Siegel, Person, et al () and van Geldern et al (), respectively. At both locations, Gustafson et al () found evidence of seaward‐dipping aquifers beneath the shelf that were contiguous with the shore.…”
Section: Discussionmentioning
confidence: 77%
“…They thus conclude that the fresh water beneath the middle shelf was most likely transported there from onshore along seaward‐dipping groundwater aquifers extending all the way to the coast, a total distance of ~50–70 km. This conclusion was recently supported by the electromagnetic study of Gustafson et al (), which was conducted at both the Martha's Vineyard and New Jersey transects studied by Siegel, Lizerralde, et al (), Siegel, Person, et al () and van Geldern et al (), respectively. At both locations, Gustafson et al () found evidence of seaward‐dipping aquifers beneath the shelf that were contiguous with the shore.…”
Section: Discussionmentioning
confidence: 77%
“…This strong conductor consistently appears in all of the initial inversion models produced by WinGLink and MARE2DEM, located in a region where the data are highly sensitive to the inversion model parameters (further information in section 4.2). Thus, we are confident that this shallow conductor is a real feature and not an inversion artifact, possibly resulting from high porosities in the thick sediments and upper crust [ Siegel et al ., ]. Resistive structures of ∼1–3k Ωm are observed horizontally between 0–75 and 150–290 km along the profile, extending vertically between ∼25 and 110 km depths (Figures a and c).…”
Section: Resultsmentioning
confidence: 95%
“…The ∼20 mGal anomaly is partially overlapping the LACZ from NNW, collocated with a vertically extended seafloor conductor that becomes significantly thicker beginning at 100 km distance along the profile, and thus, represents a thickening sediment package (Figures b and c). A seismic reflection line that coincides with our MT profile presents a thicker wedge of Pleistocene sediment beneath the profile center [ Siegel et al ., ]. Further, the LACZ and thinning lithosphere occur between ∼100 and 150 km.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent observations off of New England and New Jersey suggest that significant quantities of freshwater may exist in the subsurface beneath the shelf. In the New England area, there is evidence suggesting that fresh water forced into the subsurface beneath glaciers during lowstands (Siegel et al, 2012;2014a), and now buoyant relative to seawater, forms localized regions of overpressure in the subsurface (Siegel et al, 2014b) that may present a hazard to large structures. Offshore New Jersey, scientific drilling has confirmed the presence of fresh groundwater within confined units beneath the shelf that may be in hydrologic equilibrium with the terrestrial groundwater system (Lofi et al, 2013).…”
Section: Model Development and Validationmentioning
confidence: 99%